2015
DOI: 10.1007/s11105-015-0938-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA-size sRNAs Related to Salt Tolerance in Spirulina platensis

Abstract: microRNAs (miRNAs) are endogenous noncoding small RNAs (sRNA) that play important regulatory functions in growth, development, and environmental stress response of eukaryotes. Currently, miRNA-size sRNA (msRNAs) was discovered in several prokaryotes through deep sequencing. However, no data are available on whether msRNAs exist in cyanobacteria and whether they regulate biological tolerance to salt stress. In this study, three small RNA libraries were constructed from control (0.02 M NaCl), medium-(0.3 M NaCl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The measurement of Fragment Per Kilobase of exon per Million fragments mapped (FPKM) was applied for determining expression patterns of miRNAs among different treatments. The fold-change between different treatment groups was calculated on the basis of the equation: fold-change ¼ log 2 (treat/control); a measure commonly used to quantify changes in the expression level of a gene (Zhao et al, 2015).…”
Section: Screening Of Differential Mirnas and Prediction Of Target Genesmentioning
confidence: 99%
“…The measurement of Fragment Per Kilobase of exon per Million fragments mapped (FPKM) was applied for determining expression patterns of miRNAs among different treatments. The fold-change between different treatment groups was calculated on the basis of the equation: fold-change ¼ log 2 (treat/control); a measure commonly used to quantify changes in the expression level of a gene (Zhao et al, 2015).…”
Section: Screening Of Differential Mirnas and Prediction Of Target Genesmentioning
confidence: 99%
“…As a defense mechanism against low temperature pressure, S. platensis up-regulated the proteins involved in gluconeogenesis, amino acid biosynthesis, and starch and sucrose metabolism, whereas the translation and down-regulated tricarboxylic acid (TCA) cycle were linked to reduced energy consumption. The transcriptomic study of S. platensis was conducted at varied salinity conditions (1.17‰, 17.55‰, and 29.25‰) [17]. Zhao et al [17] confirmed the existence of msRNA in S. platensis, and these msRNA play a significant role in salt-induced stress responses.…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptomic study of S. platensis was conducted at varied salinity conditions (1.17‰, 17.55‰, and 29.25‰) [17]. Zhao et al [17] confirmed the existence of msRNA in S. platensis, and these msRNA play a significant role in salt-induced stress responses. The mechanism underlying the genes related to stress and salt tolerance has not yet been discovered.…”
Section: Introductionmentioning
confidence: 99%